A detailed design for a radioactive waste safety management system using ICT technologies. (July 2022) - Park, Hee-Seoung; Jang, Sung-Chan; Kang, Il-Sik; Lee, Dong-Ju; Kim, Jeong-Guk; Lee, Jin-Woo
Abstract: A Radioactive Waste Information Management System (RAWINGS) currently in operation mainly manages the inventory and history of the operating waste. The system has the disadvantages of the entered information needing to be transferred manually from the site to the system, information getting incorrectly entered during the process or information going missing. Recently, the Nuclear Safety and Security Commission (NSSC) and Korea Radioactive Waste Agency (KORAD) called for the development of a digital system that can show information transparently in real-time regarding the preliminary inspections of RAdioactive Waste (RAW) and the assessment of its suitability for disposal before the radioactive waste is delivered to the disposal site. A Digital Twin (DT)system is being developed for the safety management of radioactive waste to address the problems that these systems have and meet the needs of disposal operators. This paper introduces the DT technology that uses Augmented Reality (AR) technology enabling users to check the contents of small-packaged wastes in radioactive waste drums without opening them, Internet of Things (IoT) sensor technology that checks the status of the drums in the radioactive waste storage and the RAWINGS system. Based on the performance of a prototype Digital Twin consisting of three modules (AR, IoT and RAWINGS), the augmented reality enables users to see the shape information and filling rate of small-packaged wastes in the radioactive waste drums and includes Quick Response (QR) code management. The basic data of the radioactive waste used in the augmented reality, as well as small packaged wastes and repackaged drums, were processed in conjunction with RAWINGS. In addition, real-time monitoring of radioactive waste drums loaded in the designated space (Y zone: an area where combustible waste is loaded within radioactive waste storage and TEST area: a section where drums scheduled to be transported to the disposal site are loaded) of the radioactive waste storage was possible by transmitting IoT sensor signals attached to the drum to the digital twin. Currently, augmented reality has an important role in enhancing the visibility and intuitiveness of radioactive waste information for radioactive waste managers and workers by overlapping digital information about radioactive waste storage. Due to the nature of radioactive waste, it is difficult to know what waste is inside the enclosed drum. However, the results of this study confirmed that waste contained in radioactive waste drums can be identified in real time in the Digital Twin rather than in the radioactive waste storage. This technology will be useful in determining the conformity of the radioactive waste acceptance criteria required by KORAD before the delivery of radioactive waste drums to disposal sites.